2004
DOI: 10.1002/mus.20066
|View full text |Cite
|
Sign up to set email alerts
|

Infraclavicular brachial plexus injury following axillary regional block

Abstract: Infraclavicular brachial plexopathy is a potential complication of axillary regional block. We retrospectively reviewed 13 such injuries and found the median nerve most often affected, followed by combined median and ulnar neuropathies, and then by various combinations involving the median, ulnar, radial, and musculocutaneous nerves. All were axon-loss in type and most were severe in degree electrophysiologically. The clinical and electrodiagnostic features of these injuries are strikingly similar to those sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Distal pulses are often preserved because the increased intra-compartmental pressure can compress nerve microcirculation without affecting arterial blood flow. 8 Distal circulation is also protected by the extensive collateral circulation to the hand. Patients discharged from the hospital after an arteriographic study should be warned of the possibility of these delayed symptoms considering the preserved blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Distal pulses are often preserved because the increased intra-compartmental pressure can compress nerve microcirculation without affecting arterial blood flow. 8 Distal circulation is also protected by the extensive collateral circulation to the hand. Patients discharged from the hospital after an arteriographic study should be warned of the possibility of these delayed symptoms considering the preserved blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, peripheral nervous system injuries can occur through the followings: 1) direct needle trauma, 2) intraneural anesthetic injection, and 3) axillary arterial laceration. In addition, infraclavicular brachial plexus injury was reported in 0.2%-21% of the cases [4,5]. Tsao and Wilbourn [5] reported that the median nerve was most commonly affected, followed by the combined median and ulnar neuropathies in 13 cases, with brachial plexus injury after axillary BPB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, infraclavicular brachial plexus injury was reported in 0.2%-21% of the cases [4,5]. Tsao and Wilbourn [5] reported that the median nerve was most commonly affected, followed by the combined median and ulnar neuropathies in 13 cases, with brachial plexus injury after axillary BPB. In their study, medial brachial fascial compartment (MBFC) syndrome was suggested as one of the causes of median nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 This may explain why subjects in the transarterial axillary group had significantly more pain and tenderness at the site of injection when compared with the subjects in the infraclavicular block group. Our results are comparable to those of Urban and Urquhart, 1 who found that 23% of subjects receiving a transarterial axillary block complained of pain or tenderness on the first postoperative day.…”
Section: Discussionmentioning
confidence: 99%